The Influence Of Organizational Culture and Self-Efficacy On Work Motivation Of Teachers Of Civil Servants In SMP Negeri 16 Pontianak - Suparmin Suparmin; Eru Ahmadia (UNIVED Press, 2026)
This study aims to examine the influence of organizational culture and self-efficacy on the work motivation of teachers of civil servants in SMP Negeri 16 Pontianak. This study uses an associative approach with saturated sampling techniques. The sample consisted of 38 teachers of civil servants in SMP Negeri 16 Pontianak. Data analysis was carried out using multiple linear regression analysis with SPSS software version 25. The tests carried out in this study include validity tests, reliability tests, normality tests, linearity tests, and multicollinearity tests. The hypothesis test was conducted using simultaneous test (F test) and Partial Test (t test). Based on the results of hypothesis tests, both simultaneously (F test) and partially (t test), it can be concluded that organizational culture and self-efficacy together have a positive and significant influence on motivation. Partially organizational culture has no significant effect on motivation while self-efficacy has a significant effect on motivation